Allogeneic Stem Cell Transplantation in the Treatment for Transfusion-Dependent Thalassemia: Centre Experience - Pivkova Veljanovska, Aleksandra; CHadievski, Lazar; Kochoski, Bozidar; Cvetanoski, Milche; Trajkova, Sanja; Krstevska Balkanov, Svetlana; Ridova, Nevenka; Stojanoska, Simona; Mojsovska, Tara; Stojanoski, Martin; Purde, Merve; Trajkovska Anchevska, Zhaklina; et al. (Scientific Foundation Spiroski (publications), 2024)
BACKGROUND: Allogeneic stem cell transplantation (allo SCT) is still the only curative option for transfusion depended on β-thalassemia major (TDT). In patients with good risk features it is reasonable to anticipate a greater than 90% chance of a successful transplant outcome. With better risk stratification and supportive care, the results of allo-SCT have been improved even in high risk patients who have significant iron overload related organ dysfunction. Choosing the optimal conditioning regimen before allo SCT, stem cell source and focusing on transfusion free survival, as well as graft versus host disease (GVHD) free survival is a challenge in providing the quality of life in the post-transplant period for this indication. The aim of this article is to present first experience in the treatment of TDT with allo SCT from matched related donor (MRD). CASE PRESENTATION: We present a case of male patient diagnosed as thalassemia major (TM) at the age of 15 years referred at University Clinic for pediatric disease in Skopje, Republic of North Macedonia for treatment with allogeneic stem cell transplantation (allo SCT) from matched related family donor (MRD). Patients experienced two allo SCT due to early graft rejection after the first transplantation. The conditioning was done with MAC regimens, busulfan based for the first transplant and treosulfan based for the second transplant. CONCLUSION: Disease severity and the age of the patient has a crucial impact on transplant related mortality (TRM), event free survival (EFS) and the incidence of veno-oclusive liver disease as one of the main complications during SCT. More data is required on the etiology of frequent graft rejection in TDT studying the aspects of the graft and subsequent immune reconstitution that can improve the outcome of allo HSCT for thalassemia major.
Keywords: thalassemia; allogeneic stem cell transplantation; conditioning; matched related donor